Epoxy resin composite material and preparation method and composition thereof
By introducing hyperbranched amine compounds and inorganic nanoparticles into the epoxy resin, forming a three-dimensional polymer network structure and filling in inorganic nanoparticles, the problems of high dielectric constant and low thermal conductivity in electronic packaging are solved, and the effect of reducing dielectric properties and improving thermal conductivity is achieved.
Patent Information
- Application Number
- CN202410611174.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-05-16
AI Technical Summary
Epoxy resins have problems with high dielectric constant and low thermal conductivity in electronic packaging, limiting their application in high-frequency electronic devices and high-power electronic devices.
An epoxy resin composite material is adopted, which includes hyperbranched amine compounds, epoxy compounds and inorganic nanoparticles. By prepolymerization and crosslinking and doping of inorganic nanoparticles, a three-dimensional polymer network structure is formed and filled with inorganic nanoparticles to reduce the dielectric constant and improve thermal conductivity.
It effectively reduces the dielectric properties of epoxy resin materials, reduces signal delay and energy loss, improves the performance of electronic devices, and improves the heat conduction performance and enhances the heat dissipation ability of electronic devices.
Smart Images

Figure CN118638461B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic packaging materials, and in particular relates to an epoxy resin composite material and a preparation method and a composition thereof. Background Art
[0002] Epoxy resin is widely used in the field of electronic packaging. Epoxy resin is used to achieve fully enclosed packaging of electronic devices, protect electronic devices from moisture, dust, chemicals and mechanical shock, ensure the safe operation of electronic devices, enhance reliability and extend service life.
[0003] However, the epoxy resins in the related art have the following problems: on the one hand, the dielectric constant of traditional epoxy resins is relatively high, which may limit their application in high-frequency electronic devices. The high dielectric constant leads to problems of signal delay and energy loss. On the other hand, epoxy resins have low thermal conductivity, which affects their heat dissipation performance in high-power electronic devices. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an epoxy resin composite material and a preparation method and composition thereof, aiming to solve the problem of high dielectric constant and low thermal conductivity of epoxy resin.
[0005] To solve the above technical problems, the present invention is implemented as follows: an epoxy resin composite material, characterized in that it includes: a hyperbranched amine compound, an epoxy compound and inorganic nanoparticles, the mass percentage of the inorganic nanoparticles is 3%~6%, and the molar ratio of the amino group of the hyperbranched amine compound to the epoxy group of the epoxy compound is 1:1~2.
[0006] In some embodiments of the present invention, the particle size of the inorganic nanoparticles ranges from 450 to 850 nm.
[0007] In some embodiments of the present invention, the hyperbranched amine compound includes at least one of polyamidoamine, polyethyleneimine, polypropyleneimine, and polylysine;
[0008] The epoxy compound includes at least one of bisphenol A diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, and polyether diglycidyl ether;
[0009] The inorganic nanoparticles include at least one of silicon dioxide, aluminum oxide, hollow carbon and porous silicon.
[0010] The present invention also provides a preparation method for preparing the epoxy resin composite material according to any one of claims 1 to 3, characterized in that the steps include:
[0011] S1, prepolymerizing and cross-linking the hyperbranched amine compound and the epoxy compound to obtain a prepolymer;
[0012] S2, doping the inorganic nanoparticles into the prepolymer and mixing them evenly to prepare a mixture;
[0013] S3, coating the mixture and performing cross-linking molding to prepare the epoxy resin composite material.
[0014] In some embodiments of the present invention, the step S1 further comprises adding a catalyst during the pre-polymerization and cross-linking process, wherein the catalyst is at least one of dimethylamine, N-phenylpiperidine, 1-methylimidazole, and lithium hexafluorophosphate.
[0015] In some embodiments of the present invention, the mass percentage of the catalyst is 0.5-2%.
[0016] In some embodiments of the present invention, the step S1 further comprises placing the hyperbranched amine compound, the epoxy compound and the catalyst into a stirrer, with a stirring temperature of 70-90° C., a stirring rate of 200-250 r / min, and a stirring time of 60-90 min.
[0017] In some embodiments of the present invention, step S3 further includes placing the mixture in a mold or a wet film coater to coat the mixture on a metal substrate; wherein the mold material is at least one of polyethylene, polytetrafluoroethylene, and polyethylene terephthalate.
[0018] The present invention also proposes a composition, characterized in that it includes: a reversible switching group material and the epoxy resin composite material as described in any one of claims 1 to 3; wherein the reversible switching group material is one of a photosensitive group material, a heat-sensitive group material, and an electric sensitive group material.
[0019] In some embodiments of the present invention, the reversible switch group material and the epoxy resin composite material are stacked, the thickness of the reversible switch group material is 2-50 um, and the thickness of the epoxy resin composite material is 100-150 um.
[0020] Compared with the prior art, the epoxy resin composite material and the preparation method and composition thereof in the present invention have the following beneficial effects:
[0021] The present invention provides an epoxy resin composite material and a preparation method and composition thereof. The epoxy resin composite material comprises: a hyperbranched amine compound, an epoxy compound and inorganic nanoparticles. The mass percentage of the inorganic nanoparticles is 3% to 6%, and the molar ratio of the amino group of the hyperbranched amine compound to the epoxy group of the epoxy compound is 1:1 to 2. With the progress of the reaction of the epoxy compound and the hyperbranched amine compound and the continuous extension of the chain, a three-dimensional polymer network structure is formed, and a large number of cavity structures are formed inside the three-dimensional polymer network structure. The inorganic nanoparticles are filled into the cavity structure, so the inorganic nanoparticles have a lower dielectric constant and a higher specific surface area, thereby effectively reducing the dielectric properties of the epoxy resin material. The epoxy resin composite material is coated on the electronic device to reduce the signal delay and energy loss in the circuit, thereby improving the performance of the electronic device. The inorganic nanoparticles have a high thermal conductivity. The inorganic nanoparticles are filled between the hyperbranched amine compound and the epoxy compound, which improves the thermal conductivity of the epoxy resin composite material. For the use scenario of electronic packaging, the heat generated by the electronic device is effectively guided out, the temperature is reduced, and the working performance of the electronic device is improved. Moreover, due to the particularity of their structure, hyperbranched amine compounds have better rheological properties, making epoxy resin composites easier to process and use, greatly improving the bonding strength and coating effect of epoxy resin composites with electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic flow chart of a preparation method in one embodiment of the present invention;
[0023] Figure 2 Schematic diagram of the structure of a composition in one embodiment of the present invention.
[0024] In the drawings, each reference numeral indicates: 100, epoxy resin composite material; 200, reversible switch group material. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0026] Please refer to Figure 1 and Figure 2 The present invention provides an epoxy resin composite material 100, comprising: a hyperbranched amine compound, an epoxy compound and inorganic nanoparticles, the mass percentage of the inorganic nanoparticles is 3% to 6%, and the molar ratio of the amino group of the hyperbranched amine compound to the epoxy group of the epoxy compound is 1:1 to 2.
[0027] Hyperbranched amine compounds refer to molecules containing multiple amino groups, which can react with epoxy compounds to form a cross-linked network. This type of reaction is usually a ring-opening polymerization reaction, and the amino group (NH2) acts as a nucleophile close to the epoxy group of the epoxy compound. Specifically, the amino group attacks a carbon atom on the epoxy ring to form a new carbon-nitrogen bond, while opening the epoxy ring and generating a hydroxyl group (OH). The formed hydroxyl group may be deprotonated by the alkaline environment of the surrounding medium (such as the amino group itself or other catalysts) to form an oxygen anion. The newly formed negatively charged oxygen atom can further attack another epoxy group, resulting in a chain reaction.
[0028] As the above process continues, a variety of different cross-linked structures can be formed, and the progress of the reaction and the continuous extension of the chain can eventually form a three-dimensional polymer network structure. A large number of cavity structures are formed inside the three-dimensional polymer network structure, and inorganic nanoparticles are filled into the cavity structure. Therefore, the inorganic nanoparticles have a lower dielectric constant and a higher specific surface area, thereby effectively reducing the dielectric properties of the epoxy resin material. The epoxy resin composite material 100 coated on the electronic device can reduce the signal delay and energy loss in the circuit, thereby improving the performance of the electronic device. The inorganic nanoparticles enhance the mechanical strength of the epoxy resin composite material 100 and play a role in protecting the electronic device.
[0029] In addition, inorganic nanoparticles have a high thermal conductivity. Filling inorganic nanoparticles between hyperbranched amine compounds and epoxy compounds improves the thermal conductivity of the epoxy resin composite material 100. For use in electronic packaging scenarios, it can effectively conduct heat generated by electronic devices, reduce temperature, and improve the working performance of electronic devices.
[0030] The epoxy compound in the epoxy resin composite material 100 has excellent bonding ability and can be better coated on electronic devices. In addition, due to the particularity of its structure, the hyperbranched amine compounds have better rheological properties, making the epoxy resin composite material 100 easier to process and use, greatly improving the bonding strength and coating effect between the epoxy resin composite material 100 and electronic devices.
[0031] The particle size of the inorganic nanoparticles ranges from 450 to 850 nm. For example, it can be 500 nm, 600 nm, 700 nm, 800 nm, etc. When the particle size of the inorganic nanoparticles is too large, the filling rate of the inorganic nanoparticles in the prepolymer of the hyperbranched amine compound and the epoxy compound is greatly reduced, resulting in the dielectric constant of the epoxy resin being unable to meet the requirements. Therefore, the inorganic nanoparticles are within a reasonable particle size range to achieve the effective filling of the inorganic nanoparticles to the greatest extent, and effectively reduce the dielectric constant of the epoxy resin.
[0032] Specifically, the hyperbranched amine compound includes at least one of polyamide-amine, polyethyleneimine, polypropyleneimine, and polylysine; the epoxy compound includes at least one of bisphenol A diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, and polyether diglycidyl ether; and the inorganic nanoparticles include at least one of silica, alumina, hollow carbon, and porous silicon.
[0033] Embodiment 1:
[0034] Embodiment 1 of the present invention provides a preparation method for preparing an epoxy resin composite material 100, comprising the following steps:
[0035] S1. Prepolymerization and crosslinking are carried out with the molar ratio of amino group of polyethyleneimine to epoxy group of bisphenol A diglycidyl ether being 1:1 to obtain a prepolymer.
[0036] The mass of polyethyleneimine and bisphenol A diglycidyl ether was confirmed by the corresponding molar mass of the amino group of polyethyleneimine and the epoxy group of bisphenol A diglycidyl ether. The two and the catalyst were placed in a mechanical stirrer and mixed evenly. During mixing, it was necessary to ensure that the various materials were fully mixed from the bottom and edge of the container to avoid unreacted components. The catalyst used in the mixing process was dimethylamine, the mass percentage of the catalyst was 2%, the speed of the mechanical stirrer was 250r / min, the stirring temperature was 90°C, and the stirring time was 60min.
[0037] Mixing the epoxy compound and the hyperbranched amine compound first can ensure that they are fully mixed at the microscopic level, which is conducive to the uniformity of the curing reaction and avoids the formation of unreacted areas. The low viscosity of the mixture of the two helps to achieve a better mixing effect. In addition, the curing reaction will gradually increase the viscosity of the system, so the best stirring effect is easier to achieve in the early stage of the reaction. Adding a catalyst such as dimethylamine can effectively reduce the activation energy of the prepolymer, thereby accelerating the curing speed and increasing the crosslinking density.
[0038] S2, adding silicon dioxide to the prepolymer and mixing them evenly to prepare a mixture, wherein the particle size of the silicon dioxide is 500 nm, the mass percentage of the silicon dioxide is 6%, and the stirring time is 120 min.
[0039] Adding inorganic nanomaterials after the prepolymer is slightly solidified and the viscosity increases can help the inorganic nanomaterials to be better dispersed in the prepolymer, because the system viscosity is moderate at this time, which is conducive to breaking up the agglomeration of inorganic nanoparticles. Adding inorganic nanomaterials too early may cause sedimentation during the curing process, while adding them later can reduce this risk, thereby obtaining a more uniform distribution of inorganic nanomaterials.
[0040] Reacting the epoxy compound with the hyperbranched amine compound first can form a more uniform cross-linked network, which helps control the mechanical properties and thermal stability of the composite material. The inorganic nanomaterials added later will be more evenly distributed in the partially cured epoxy compound, resulting in better reinforcement and dielectric properties. The optimized mixing order helps to improve the interfacial compatibility between the epoxy matrix and the inorganic nanoparticles and enhance the interfacial bonding through physical and chemical interactions.
[0041] S3, coating the mixture and performing cross-linking molding to prepare the epoxy resin composite material 100.
[0042] Specifically, the mixture is placed in a wet film applicator and coated on a tin-plated steel plate. The wet film applicator is used to accurately apply a layer of coating or coating with a specific thickness on a flat substrate surface. By controlling the orifice size of the wet film applicator, a wet coating with uniform thickness can be accurately prepared. The specific structure of the wet film applicator is the same as that of the prior art, and will not be described again.
[0043] The mixture is coated on a metal substrate such as tinplate to form a coating. The metal substrate can provide a very flat surface, which is essential for ensuring the uniformity and finish of the coating. The metal substrate has good chemical resistance to most chemicals, especially commonly used solvents and curing agents. Metal substrates usually have excellent thermal conductivity and high temperature resistance, which helps to evenly distribute heat to the entire area of the coating during the coating curing process, and is suitable for post-coating heat treatment processes such as heat curing and annealing.
[0044] Moreover, metal surfaces can often be treated with appropriate surface treatments, such as coating release agents or using specific processing techniques, to ensure that the epoxy resin film can be easily peeled off after curing without leaving residue. Metal substrates usually have high mechanical strength and rigidity, which can provide sufficient support to maintain the integrity of the coating during preparation and subsequent processing.
[0045] Specifically, the cross-linking molding can be carried out in a heating plate or a heating box. In this embodiment, the cross-linking molding heating temperature is 150°C and the heating time is 120 minutes. The formed epoxy resin composite material 100 can be peeled off from the metal substrate to facilitate subsequent processing. The thickness of the prepared epoxy resin composite material 100 is 150um.
[0046] Embodiment 2:
[0047] Embodiment 2 of the present invention provides a preparation method for preparing an epoxy resin composite material 100, comprising the following steps:
[0048] S1. Prepolymerization and crosslinking are carried out with a molar ratio of amino groups of polyamide-amine to epoxy groups of ethylene glycol diglycidyl ether being 1:1.2 to obtain a prepolymer.
[0049] Put polyamide-amine, ethylene glycol diglycidyl ether and catalyst into a mechanical stirrer and mix them evenly. When mixing, ensure that the various materials are fully mixed from the bottom and edge of the container to avoid unreacted components. Among them, the catalyst used in the mixing process is N-phenylpiperidine, the mass percentage of the catalyst is 1.5%, the speed of the mechanical stirrer is 230r / min, the stirring temperature is 80°C, and the stirring time is 80min.
[0050] S2. Aluminum oxide is doped into the prepolymer and mixed evenly to prepare a mixture, wherein the particle size of the aluminum oxide is 500 nm, the mass percentage of the aluminum oxide is 5%, and the stirring time is 90 minutes.
[0051] S3, coating the mixture and cross-linking the mixture to form an epoxy resin composite material 100. The mixture is placed in a mold and coated on a metal substrate; wherein the cross-linking heating temperature is 150° C., the heating time is 150 min, and the thickness of the epoxy resin composite material 100 is 180 μm.
[0052] The abrasive material is polytetrafluoroethylene. Polytetrafluoroethylene is non-sticky, which means that paint or other sticky substances will not easily adhere to the tool surface, making the coating process cleaner, continuous and efficient. This feature also makes coating tools easier to clean and maintain. In addition, polytetrafluoroethylene has excellent chemical stability and is inert to almost all chemical reagents. This allows it to handle coatings of various chemical compositions without reacting, ensuring that the purity and performance of the coating are not affected.
[0053] PTFE is also able to withstand higher temperatures, which is especially important for coatings that need to be applied or cured at higher temperatures. Using coating tools ensures that the tools will not be damaged even if they are exposed to high temperatures during the coating process. PTFE has an extremely low coefficient of friction, which allows it to slide more smoothly over the substrate surface during the coating process, reducing mechanical stress on the substrate, which is especially important when coating soft or sensitive materials. Although PTFE is inherently soft, it has good wear resistance and is suitable for long-term use. It is not easily worn away by the coating material, which maintains the accuracy and life of the coating tool.
[0054] Embodiment 3:
[0055] Embodiment 3 of the present invention provides a preparation method for preparing an epoxy resin composite material 100, comprising the following steps:
[0056] S1. Prepolymerization and crosslinking are carried out with a molar ratio of amino groups of polypropylene imine and epoxy groups of propylene glycol diglycidyl ether being 1:1.5 to obtain a prepolymer.
[0057] Put polypropylene imine, propylene glycol diglycidyl ether and catalyst into a mechanical stirrer and mix them evenly. When mixing, ensure that the various materials are fully mixed from the bottom and edge of the container to avoid unreacted components. Among them, the catalyst used in the mixing process is 1-methylimidazole, the mass percentage of the catalyst is 1%, the speed of the mechanical stirrer is 200r / min, the stirring temperature is 80℃, and the stirring time is 70min.
[0058] S2, adding hollow carbon to the prepolymer and mixing them evenly to prepare a mixture, wherein the particle size of the hollow carbon is 700 nm, the mass percentage of the hollow carbon is 4%, and the stirring time is 60 min.
[0059] S3, coating the mixture and cross-linking the mixture to form an epoxy resin composite material 100. The mixture is placed in a mold and coated on a metal substrate; wherein the cross-linking heating temperature is 150° C., the heating time is 180 min, and the thickness of the epoxy resin composite material 100 is 200 um.
[0060] The abrasive material is polyethylene, which also has non-stick properties, is chemically inert to most solvents and chemicals, and can be used over a wide temperature range.
[0061] Embodiment 4:
[0062] Embodiment 4 of the present invention provides a preparation method for preparing an epoxy resin composite material 100, comprising the following steps:
[0063] S1. Prepolymerization and crosslinking are carried out with a molar ratio of amino groups of polylysine and epoxy groups of polyether diglycidyl ether being 1:2 to obtain a prepolymer.
[0064] Put polylysine, polyether diglycidyl ether and catalyst into a mechanical stirrer and mix them evenly. When mixing, ensure that the various materials are fully mixed from the bottom and edge of the container to avoid unreacted components. The catalyst used in the mixing process is lithium hexafluorophosphate, the mass percentage of the catalyst is 0.5%, the speed of the mechanical stirrer is 200r / min, the stirring temperature is 70°C, and the stirring time is 60min.
[0065] S2, doping the hollow carbon into the prepolymer and mixing them evenly to prepare a mixture, wherein the particle size of the hollow carbon is 800 nm, the mass percentage of silicon dioxide is 3%, and the stirring time is 60 minutes.
[0066] S3, coating the mixture and cross-linking the mixture to form an epoxy resin composite material 100. The mixture is placed in a mold and coated on a metal substrate; wherein the cross-linking heating temperature is 180° C., the heating time is 180 min, and the thickness of the epoxy resin composite material 100 is 250 um.
[0067] The abrasive material is polyethylene terephthalate, which also has non-adhesive properties, good chemical stability and wear resistance, and good high temperature resistance.
[0068] Comparative Example 1:
[0069] The preparation method of the epoxy resin composite material 100 of Comparative Example 1 is different from that of Example 1 in that the epoxy compound, the hyperbranched amine compound and the inorganic nanoparticles are directly mixed and stirred.
[0070] Comparative Example 2:
[0071] The preparation method of the epoxy resin composite material 100 of Comparative Example 2 is different from that of Example 1 in that the mass percentage of the inorganic nanoparticles is 10%.
[0072] Comparative Example 3:
[0073] The preparation method of the epoxy resin composite material 100 of Comparative Example 3 is different from that of Example 1 in that the particle size of the inorganic nanoparticles is 1000 nm.
[0074] Comparative Example 4:
[0075] The preparation method of the epoxy resin composite material 100 of Comparative Example 4 is different from that of Example 1 in that in step S1 , the stirring temperature is 120° C.
[0076] Comparative Example 5:
[0077] The preparation method of the epoxy resin composite material 100 of Comparative Example 5 is different from that of Example 1 in that in step S1 , the stirring temperature is 50° C.
[0078] Comparative Example 6:
[0079] The preparation method of the epoxy resin composite material 100 of Comparative Example 5 is different from that of Example 1 in that no catalyst is added during step S1.
[0080] Experiment 1: Determination of the internal component morphology of the epoxy resin composite material 100.
[0081] After the epoxy resin composite materials 100 obtained in the above-mentioned Examples 1-4 and Comparative Examples 1-6 were sliced, the slices were observed and measured using SEM.
[0082] Table 1, morphology comparison table of each embodiment and comparative example:
[0083]
[0084] According to Table 1 above:
[0085] The inorganic nanoparticles on the cut surface of the epoxy resin composite material 100 of Example 1-4 are evenly distributed, indicating that the epoxy resin composite material 100 prepared using the preparation method of the present invention has a good morphology and a good structure. In Comparative Example 1, epoxy compound, hyperbranched amine compound and inorganic nanoparticles are directly mixed and stirred. The order of first mixing epoxy compound and hyperbranched amine compound and then adding inorganic nanoparticles is not followed, resulting in uneven dispersion of inorganic nanoparticles and aggregation. The dielectric constant of the epoxy resin composite material 100 finally prepared is high, and the thermal conductivity is low, which affects the protective performance and thermal conductivity. Stirring multiple components together directly is also not conducive to the dispersion of hyperbranched amine compounds, resulting in a decrease in the number of cavities that appear, further affecting the aggregation of inorganic nanoparticles.
[0086] The mass percentage of inorganic nanoparticles in Comparative Example 2 is 10%. The proportion in the epoxy resin composite material 100 is too high, and it is difficult to disperse evenly after stirring, which affects the performance. The particle size of the inorganic nanoparticles in Comparative Example 3 is 1000nm. The particle size of the inorganic nanoparticles is too large, and the excessively large particle size leads to a smaller contact area between the inorganic nanoparticles and other particles or solvent molecules in the composite material, making the interaction between the particles stronger and increasing the tendency to aggregate.
[0087] In comparative example 4, during step S1, the stirring temperature is 120°C. The stirring temperature is too high, resulting in too high a degree of curing of the epoxy compound and the hyperbranched amine compound, and too large a viscosity of the prepolymer, which affects the dispersion of the inorganic nanoparticles in the composite material. In comparative example 5, during step S1, the stirring temperature is 50°C. The stirring temperature is too low, resulting in too low a viscosity of the prepolymer, and the inorganic nanoparticles settle and aggregate therein. At the same time, the lower temperature causes the cross-linking molding time to be too long, resulting in the collapse of the internal cavity, which further leads to the aggregation of the inorganic nanoparticles. In comparative example 6, no catalyst is added during step S1. The curing time increases, the cross-linking density decreases, the cavity decreases, and the inorganic nanoparticles aggregate.
[0088] The phenomenon of cavity reduction and inorganic nanoparticle aggregation in the above comparative example will lead to a decrease in the protection performance and thermal conductivity of the epoxy resin composite material 100 .
[0089] Experiment 2: Determination of the dielectric constant of the epoxy resin composite material 100.
[0090] The epoxy resin composite material 100 obtained in the above-mentioned embodiments 1-4 and comparative examples 1-6 is measured for dielectric constant by an impedance analyzer. The epoxy resin composite material 100 is cut and placed in the impedance analyzer, and an appropriate measurement frequency range, signal level and measurement time are set on the impedance analyzer. According to the geometric dimensions of the cut sample, the measurement frequency and the capacitance value, the dielectric constant of the material is calculated using the formula: wherein ε can be calculated according to the capacitance C of the material, the thickness d of the sample and the electrode area A according to ε= Cd / (ε0A), wherein ε0 is the dielectric constant in a vacuum, ε0=8.854187817×10 -12 F / m.
[0091] Table 2, dielectric constant comparison table of each embodiment and comparative example:
[0092]
[0093] According to Table 2 above, we can know that:
[0094] The dielectric constants of the epoxy resin composite materials 100 of Examples 1-4 are all smaller than those of Comparative Examples 1-6, indicating that the epoxy resin composite materials 100 prepared according to the preparation method of the present invention have the characteristics of low dielectric constant, effectively reducing the interconnection delay, crosstalk and energy consumption between electronic devices, and playing a role in electronic protection.
[0095] The inorganic nanoparticles in the epoxy resin composite materials 100 of comparative examples 1-6 aggregate, and these aggregates will change the dielectric properties of the material because they form particle phases with different dielectric properties on a microscopic scale. The number of interfaces between the inorganic nanoparticles and the epoxy resin matrix will decrease as the particle aggregation increases, resulting in a weakened interface polarization effect, and defects or discontinuities at the interface may cause the macroscopic dielectric properties of the material to deteriorate. In addition, the aggregated inorganic nanoparticles will cause the electric field distribution in the composite material to be uneven, which may increase the dielectric loss in the high electric field area, thereby increasing the dielectric constant.
[0096] Experiment 3: Determination of thermal conductivity of epoxy resin composite material 100. The thermal conductivity of epoxy resin composite material 100 obtained in the above-mentioned Examples 1-4 and Comparative Examples 1-6 was measured by a thermal conductivity measuring instrument. The epoxy resin composite material 100 was cut into test pieces and placed in the thermal conductivity measuring instrument. The test temperature and test time of the thermal conductivity were set. The calculation formula was φ=-λA*(dt / dx), where φ is the heat flow, λ is the thermal conductivity, A is the area of the test piece, and t is the test time.
[0097] Table 3, thermal conductivity comparison table of each embodiment and comparative example:
[0098]
[0099] According to Table 3 above:
[0100] The thermal conductivity coefficients of the epoxy resin composite materials 100 of Examples 1-4 are all smaller than those of Comparative Examples 1-6, indicating that the epoxy resin composite materials 100 prepared according to the preparation method of the present invention have better thermal conductivity, and the inorganic nanoparticles have better thermal conductivity than the resin matrix. When these particles are evenly distributed in the epoxy resin matrix, a continuous thermal conductivity path can be formed, thereby effectively improving the overall thermal conductivity of the epoxy resin composite material 100.
[0101] However, the inorganic nanoparticles in the epoxy resin composite materials 100 of Comparative Examples 1-6 are aggregated, and the inorganic nanoparticles in the aggregated state cannot form an effective continuous heat conduction path, so the thermal conductivity is lower than that of the uniformly distributed particles. When the inorganic nanoparticles are aggregated, the interface thermal resistance may be superimposed in the aggregated area to form a larger thermal resistance, thereby reducing the overall thermal conductivity of the material.
[0102] The present invention also proposes a composition, characterized in that it includes: a reversible switch group material 200 and an epoxy resin composite material 100; wherein the reversible switch group material 200 is one of a light-sensitive group material, a heat-sensitive group material, and an electric-sensitive group material.
[0103] The main feature of the reversible switch group material 200 is that it can be reversibly transformed under specific conditions, and these conditions can be light, heat, electricity or other stimuli. The light-sensitive group material can be azobenzene, which can be converted from trans to cis under the action of light, especially ultraviolet light, changing its polarity and electronic configuration. Or cadmium sulfide, which can change its electronic structure and dielectric properties under light of a specific wavelength. The heat-sensitive group material can be a thermochromic material, which can change its structure and electrical properties when a specific temperature is reached. Or a shape memory polymer, which can be transformed from one form to another after heating, while affecting the dielectric properties of the material. The electrosensitive group can be barium titanate, whose polarization state can be adjusted by an external electric field, thereby changing the dielectric properties of the material.
[0104] In one embodiment of the invention, the reversible switch group material 200 and the epoxy resin composite material 100 can be synthesized into the epoxy compound, and then pre-polymerized and cross-linked with the hyperbranched amine compound, and then inorganic nanoparticles are added to mix evenly and solidified.
[0105] In one embodiment of the present invention, physical vapor deposition or chemical vapor deposition technology can be performed on the epoxy resin composite material 100 after molding to deposit a thin film on the surface, the thin film containing the required reversible switch group to achieve very precise control of the reversible switch group, or a coating containing the reversible switch group can be coated on the epoxy resin composite material 100 by coating, spraying, etc. Through the above method, the polarity conversion of the reversible switch group can be triggered by external stimulation to achieve dynamic regulation of dielectric properties.
[0106] Specifically, the reversible switch group material 200 and the epoxy resin composite material 100 are stacked, the thickness of the reversible switch group material 200 is 2-50 um, and the thickness of the epoxy resin composite material 100 is 100-150 um. Preferably, the thickness of the reversible switch group is 5 um, and the thickness of the epoxy resin composite material 100 is 150 um.
[0107] In one embodiment of the present invention, the composition can be applied to electronic devices for electronic packaging. The packaging method can first generate the epoxy resin composite material 100 on the surface of the electronic device through coating, deposition, spraying, etc., and then generate the reversible switch group material 200 on the epoxy resin composite material 100 to ensure that the reversible switch group can accurately receive external stimuli, thereby regulating the dielectric properties, improving the accuracy of adjustment, and reducing errors.
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An epoxy resin composite material, characterized in that: include: A hyperbranched amine compound, an epoxy compound and inorganic nanoparticles, wherein the mass percentage of the inorganic nanoparticles is 3% to 6%, and the molar ratio of the amino group of the hyperbranched amine compound to the epoxy group of the epoxy compound is 1:1 to 2; Wherein, the preparation method of the epoxy resin composite material comprises: S1, prepolymerizing and cross-linking the hyperbranched amine compound and the epoxy compound to obtain a prepolymer; S2, doping the inorganic nanoparticles into the prepolymer and mixing them evenly to prepare a mixture; S3, coating the mixture and performing cross-linking molding to prepare the epoxy resin composite material.
2. The epoxy resin composite material according to claim 1, characterized in that: The particle size of the inorganic nanoparticles ranges from 450 to 850 nm.
3. The epoxy resin composite material according to claim 1, characterized in that: The hyperbranched amine compound includes at least one of polyamide-amine, polyethyleneimine, polypropyleneimine, and polylysine; The epoxy compound includes at least one of bisphenol A diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, and polyether diglycidyl ether; The inorganic nanoparticles include at least one of silicon dioxide, aluminum oxide, hollow carbon and porous silicon.
4. The epoxy resin composite material according to claim 1, characterized in that: The step S1 further comprises adding a catalyst during the prepolymerization and cross-linking process, wherein the catalyst is at least one of dimethylamine, N-phenylpiperidine, 1-methylimidazole, and lithium hexafluorophosphate.
5. The epoxy resin composite material according to claim 4, characterized in that: The mass percentage of the catalyst is 0.5-2%.
6. The epoxy resin composite material according to claim 4, characterized in that: The step S1 further comprises placing the hyperbranched amine compound, the epoxy compound and the catalyst into a stirrer, with a stirring temperature of 70-90° C., a stirring rate of 200-250 r / min, and a stirring time of 60-90 min.
7. The epoxy resin composite material according to claim 4, characterized in that: The step S3 further comprises placing the mixture in a mold or a wet film coater to coat the mixture on a metal substrate; wherein the mold material is at least one of polyethylene, polytetrafluoroethylene, and polyethylene terephthalate.
8. A composition, characterized in that include: A reversible switch group material and an epoxy resin composite material as claimed in any one of claims 1 to 7; wherein, The reversible switch group material is one of a light-sensitive group material, a heat-sensitive group material, and an electric-sensitive group material.
9. The composition according to claim 8, characterized in that The reversible switch group material and the epoxy resin composite material are stacked, the thickness of the reversible switch group material is 2-50 um, and the thickness of the epoxy resin composite material is 150-250 um.
Citation Information
Patent Citations
Medium insulation coating, preparation method thereof and solid insulation component
CN115213071A